Clinical And Radiological Evaluation Of Ankle Morbidity Following Long Segment Fibula Graft Harvesting - Ibrahim, Mohd Yusof (2001)
Fibular graft is a useful technique to restore skeletal integrity of bony defects. Despite the benefits of this procedure, there are some reported problems associated with donor site, particularly with regards to ankle stability.